Engagement Mediates the Relationship Between Emotion and Achievement of Chinese EFL Learners - Feng, Enhao; Hong, Gang (Frontiers in Psychology, 2022)
Emotion and engagement are fundamental in second language acquisition. However, relevant research is scant. The present study narrows the research gap by investigating the correlations between achievement emotions, behavioral engagement, and self-reported English achievements. 633 students from four senior high schools in China participate in the study. Data elicited through questionnaires reveal: 1) Participants have a medium to high level of foreign language enjoyment (FLE) foreign language classroom anxiety (FLCA), and behavioral engagement; females have a higher level of FLE and behavioral engagement than males; the participants feel more anxiety and less enjoyment than international samples; 2) significant correlations are found between FLE, FLCA, behavioral engagement, and self-reported achievement; 3) significant mediating effects of behavioral engagement are found between both achievement emotions (FLE and FLCA) and self-reported achievement, and the mediating effect is stronger between FLCA and self-reported achievement. The findings extend the nomological network of achievement emotions, develop our insights into the complex relationships between emotions and learner engagement, and reveal the underlying mediating effects of behavioral engagement. Finally, directions for future study and implications for EFL teachers in Chinese senior high schools are provided.